2019
DOI: 10.1088/1757-899x/518/2/022043
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Shear Strength and Volume Changes of Expansive Soils Utilizing Different Additives

Abstract: Some clayey soils are generally classified as expansive soils which cause extensive damage to civil engineering structures due to change in its water content and the amount and type of clay size particles. Other important factors affecting the expansion behavior include the amount of non-expansive materials. This paper based on comparing two solutions to improve the soil parameters: the first solution to improve the soil with steel fiber and the second solution to improve the soil strength and volume changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The increase in LL with higher proportion of plastic strips could be a result of the reduced friction in the soil, due to excess amount of plastic strips added to the soil which act as a lubricant and result in easier movement of the soil particles resulting in higher liquid limits. Similar findings of decrease in LL and swelling percentage of the treated soil with plastic strips has been stated in literatures [1,[38][39]. The observed increase in liquid limit (LL) with higher sisal fiber content can be attributed to the water absorption capacity of sisal.…”
Section: Effect Of Plastic Strips/sisal Fiber and Cement On The Liqui...supporting
confidence: 89%
“…The increase in LL with higher proportion of plastic strips could be a result of the reduced friction in the soil, due to excess amount of plastic strips added to the soil which act as a lubricant and result in easier movement of the soil particles resulting in higher liquid limits. Similar findings of decrease in LL and swelling percentage of the treated soil with plastic strips has been stated in literatures [1,[38][39]. The observed increase in liquid limit (LL) with higher sisal fiber content can be attributed to the water absorption capacity of sisal.…”
Section: Effect Of Plastic Strips/sisal Fiber and Cement On The Liqui...supporting
confidence: 89%
“…The results showed that the three soils' LLs decreased by about 11%-18% with the addition of 9% RHA, while the PI reduced by about 32%-80%, and the soil's rice husk content increased to its maximum at RHA between 6% and 8%. Irshayyid and Fattah [26] compared two methods for enhancing the parameters of the soil: the first method used steel fibers to enhance the soil, and the second method used plastic waste to enhance the strength and volume fluctuations of the soil. The effects of adding varying amounts of steel fiber and plastic trash (4%, 8%, and 12%) by dry weight of soil were investigated in a number of tests.…”
Section: Introductionmentioning
confidence: 99%
“…Because clayey soils volume change behavior is so sensitive to moisture content, expansive soils are used difficult in engineering applications [2]. A variety of soil stabilization techniques have been used to stabilize expansive soil, including fly ash [11] RBI Grade-81 [12], Steel fiber [13], Rice husk [14], glass fiber [15][16][17][18][19][20][21][22][23][24][25][26], bagasse ash [4] [27-28], lime [27, [29][30], cement [26,31], corn straw ash [32], Polypropylene Fiber [10,18,33], Basalt Fiber [34], Coir Fiber [35], Sisal Fibre [36], Jute Fiber [37] and Plastic Waste Powder [38] etc. When the area to be treated is limited, reinforcements are especially trustworthy and successful at strengthening weak soil.…”
Section: Introductionmentioning
confidence: 99%